Modelling Foundations and Applications 7th European Conference, ECMFA 2011, Birmingham, UK, June 6 - 9, 2011 Proceedings - France, Robert B.; Kuester, Jochen M.; Bordbar, Behzad; Paige, Richard F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 7th European Conference on Modelling Foundations and Applications, held in Birmingham, UK, in June 2011. The 19 revised full foundations track papers and 5 revised full applications track papers presented were carefully reviewed and selected from 61 submissions; also included are 5 workshop summaries and abstracts of 4 tutorials. The papers are organized in topical sections on model execution, model analysis, methodology, model management, model transformation, variability analysis and ADLs, and domain-specific modeling.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Management of Computing and Information Systems; Programming Techniques